2017
DOI: 10.1016/j.seizure.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Welfare consequences for people with epilepsy and their partners: A matched nationwide study in Denmark

Abstract: Epilepsy has major socioeconomic consequences for individual patients, their partners and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
4
21
0
2
Order By: Relevance
“…The mortality rate of SDRE in patients within 3 years was 14%, which is seven times the rate for a control population matched for age and gender. The increased mortality is high and in line with a recently published, matched nationwide study from Denmark reporting mortality among epilepsy patients of more than 10% 3 years after diagnosis of epilepsy ( 53 ). Causes of death among people with epilepsy are manifold.…”
Section: Discussionsupporting
confidence: 86%
“…The mortality rate of SDRE in patients within 3 years was 14%, which is seven times the rate for a control population matched for age and gender. The increased mortality is high and in line with a recently published, matched nationwide study from Denmark reporting mortality among epilepsy patients of more than 10% 3 years after diagnosis of epilepsy ( 53 ). Causes of death among people with epilepsy are manifold.…”
Section: Discussionsupporting
confidence: 86%
“…We found a higher mortality rate in this small population of patients with PNES than in controls. Several factors are responsible for the elevated mortality rates found in childhood, adolescent, and adult epilepsy [1,34], including seizure severity, underlying diseases, medication, comorbidities, and life-style factors [35][36][37]. A previous study also reported greater mortality in PNES [38].…”
Section: Discussionmentioning
confidence: 94%
“…Epilepsy is characterized by frequent and unpredictable disruptions of brain functions resulting in “epileptic seizures.” Epilepsy has a great impact on the quality of life through increased incidence of injury and death, unemployment rates, lower monthly incomes, higher household costs and high absenteeism at work and schools (Jennum et al, 2017 ; Trinka et al, 2018 ; Wibecan et al, 2018 ). An epileptic seizure is considered as a transient episode of signs or symptoms, including transitory confusion, staring speech, irrepressible jerking movements, loss of consciousness, psychic symptoms such as fear and anxiety, due to the abnormal synchronous neuronal activity of the brain.…”
Section: Introductionmentioning
confidence: 99%